Strain sensors based on conducting poly(acrylamide) hydrogels. (2020) - Künzel, Matthias; Panhuis, Marc in het
ABSTRACT: A simple model system towards an impedance-probing strain sensor based on conducting tough hydrogels is demonstrated. A poly(acrylamide) hydrogel, cross-linked with N, N'-methylene-bis(acrylamide) was contacted with carbon fibres for electrical impedance analysis. The conductivity of the salt-containing hydrogel was determined to be 114 ± 10 mS/cm. Upon stretching the hydrogel samples to their fourfold initial length, the impedance response increased according to a power law. This was used to establish a sensing equation for the relation between the resistive component of the impedance signal and the applied mechanical strain under tension. This work contributes to the development of highly stretchable and soft strain sensors for applications in soft robotics.